Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/jf203187v
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Healthful Lipid Constituents of Commercially Important Tree Nuts

Abstract: Uncharacteristic of most whole foods, the major component of tree nuts is lipid; surprisingly, information on the lipid constituents in tree nuts has been sporadic and, for the most part, not well reported. Most published papers focus on only one nut type, or those that report a cultivar lack a quality control program, thus making data comparisons difficult. The present study was designed to quantify the healthful lipid constituents of 10 different types of commercially important tree nuts (i.e., almonds, blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 45 publications
17
71
1
Order By: Relevance
“…Pistachios contained appreciable amounts of c-tocotrienol (c-T3; 1.9-2.4 mg 100 g À1 ), whereas a-tocotrienol (a-T3) was the only isoform identified in macadamia nuts (1.8-2.8 mg 100 g À1 ). The tocopherol and tocotrienol contents in our nut varieties were comparable to levels reported in other studies (Kornsteiner, Wagner, & Elmadfa, 2006;Lux et al, 2012;Robbins et al, 2011), though the absolute values differed, likely due to varying cultivation conditions. The present study reveals that the different roasting conditions affected the content of the distinct vitamin E isoforms differentially.…”
Section: Tocopherols and Tocotrienolssupporting
confidence: 87%
See 2 more Smart Citations
“…Pistachios contained appreciable amounts of c-tocotrienol (c-T3; 1.9-2.4 mg 100 g À1 ), whereas a-tocotrienol (a-T3) was the only isoform identified in macadamia nuts (1.8-2.8 mg 100 g À1 ). The tocopherol and tocotrienol contents in our nut varieties were comparable to levels reported in other studies (Kornsteiner, Wagner, & Elmadfa, 2006;Lux et al, 2012;Robbins et al, 2011), though the absolute values differed, likely due to varying cultivation conditions. The present study reveals that the different roasting conditions affected the content of the distinct vitamin E isoforms differentially.…”
Section: Tocopherols and Tocotrienolssupporting
confidence: 87%
“…Despite slight variations, the lipid composition of raw and roasted nuts is in line with values reported by Robbins et al (2011) who analysed lipid constituents of ten different tree nuts, including hazelnuts, almonds, macadamia nuts, pistachios and walnuts. The authors also pointed out that variations could be due to differences regarding the cultivars and growth conditions.…”
Section: Fatty Acidssupporting
confidence: 87%
See 1 more Smart Citation
“…From a placebo-controlled, three-way crossover design clinical trial with a one-week washout period between pecan treatments, Hudthagosol et al (2011) reported that γ-tocopherol and the proanthocyanidin (PAC) flavan-3-ol monomers of pecans were absorbable and contributed to postprandial antioxidant defenses in the human body. The increased interest in pecans is partially due to their healthful lipid components (i.e., fatty acids, tocopherol homologues, and phytosterols) (Robbins, Shin, Shewfelt, Eitenmiller, & Pegg, 2011), but it is also associated with their beneficial phenolics and PAC content (Amarowicz, Troszyń ska, & Shahidi, 2005). Reactive oxygen species (ROS) are free radicals found naturally in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Pecans are unique in that a significant portion of their Ts (89.4 %) are represented by the γ-T homologue (Robbins et al, 2011). From a health standpoint, γ-T is considered important because it has been shown to be a better free-radical scavenger than α-T (Christen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%